Morphometry of the adult human dry hip bone in Kashmiri population - Kausar, Zeenat; Bhat, Ghulam Mohammad; Shahdad, Shaheen; Bashir, Khalid (International Journal of Research in Medical Sciences, 2018)
Background: The distinctive morphology of the human hip bone makes it of interest from anatomical, anthropological and forensic point of view. Thus, by using visual criteria, metric techniques and discriminant function analysis we can estimate the age, sex and race of an individual. Objective was to do the morphometry of 60 dry human hip bones in Kashmiri population in order to evaluate the various parameters of the hip bone. Methods: The study was done on 60 randomly collected Kashmiri adult unpaired hip bones of unknown sex to analyse and evaluate the weight, length, width and the Coxal index of hip bone. All the hip bones selected were dry, complete and showed normal anatomical features. Specimens showing osteoarthritic changes, evidence of any previous trauma or skeletal disorders was excluded from the study. Results: The raw data obtained was statistically analysed. Range, mean, standard deviation and standard error of mean were determined for each parameter. All values were compared with series of other workers to draw the conclusions. Conclusions: From this study, it was concluded that right hip bone has larger parameters and greater strength of skeletal elements. The difference seen between the values of present study and that of other workers could be explained on the basis of ethnic and racial variations.